Adaptive Tracking Control for a Class of Stochastic Uncertain Nonlinear Systems With Input Saturation - Gao, Yong-Feng; Sun, Xi-Ming; Wen, Changyun; Wang, Wei (IEEE transactions on automatic control, 2017)
In this technical note, the problem of adaptive tracking control is investigated for a class of stochastic uncertain nonlinear systems in the presence of input saturation. To analyze the effect of input saturation, an auxiliary system is employed. With the help of backstepping technique, an adaptive stochastic tracking control approach is developed. Under the proposed adaptive tracking controller, the boundedness of all the signals in the closed-loop system is achieved almost surely. Moreover, distinct from most of the existing results, the ultimate tracking error can be bounded by an explicit function of design parameters and input saturation error (the error between the control input and saturated input) in the mean quartic sense. Finally, an example is given to show the effectiveness of the proposed scheme.